Design of Plane Wave Generator Based on Strong Robust Inverse Radiation Problem Solving Method - HuYan, Siteng; Chen, Wei; Wang, Shiquan; Du, Liuge; Zhao, Jia (Frontiers in Physics, 2022)
In this manuscript, we reconsider the amplitude and phase combination of the PWG from an electromagnetic field inverse radiation perspective and further propose a new method based on the Gauss-Newton inversion (GNI) to perform the inverse design of PWG. Furthermore, the wideband antenna pattern is applicated of in the transfer function makes the inversion results closer to the engineering implementation. Compared with the traditional least-squares method (LSM) and singular value decomposition (SVD) method, the proposed method owns the merits of less amplitude range of the input source and stronger robustness.